Digital Competencies for Science Teaching: Adapting the DiKoLAN Framework to Teacher Education in Switzerland - Thoms, Lars-Jochen; Colberg, Christina; Heiniger, Peter; Huwer, Johannes (Frontiers in Education, 2022)
Prospective teachers need both general and subject-specific digital competencies. However, available competency frameworks usually address only non-subject-specific general digital competencies. Although the joint framework curriculum of the German-speaking cantons of Switzerland not only provides a comprehensive definition of expected digital student competencies, but also suggestions for linking them to and implementing them in subject lessons, there is still no integral planning and structuring for subject-specific teacher training in the canton of Thurgau. For a curricular design of the promotion of subject-specific digital competencies, three competency frameworks for the study programs Primary level, Secondary level 1 and Secondary level 2 at the Thurgau University of Teacher Education were derived in expert interviews based on the DiKoLAN framework (Digital Competencies for Science Teaching). While there are significant overlaps, the original reference framework clearly needs to be adapted. Furthermore, there are important commonalities between the newly formed individual competency frameworks. The methodological approach has proven to be fruitful and is recommended to follow-up studies and studies with similar research questions for imitation.